Efficacy and safety of empiric treatment with omeprazole continuous infusion in critically ill children with gastrointestinal bleeding - Taher, Khalid W.; Yaseen, Rahaf; Alnan, Mayas; Aburas, Wejdan; Khalil, Hala; Alabdulsalam, Moath (Frontiers in Pediatrics, 2024)
Introduction Gastrointestinal bleeding (GI) is a prevalent condition among pediatric patients, with a reported incidence of 6.4%, often severe enough to require admission to the pediatric intensive care unit (PICU). There are multiple therapies utilized in the management of GI bleeding in pediatrics, among which continuous intravenous (IV) infusion of omeprazole is used off-label without standard pediatric dosing recommendations. Reviewing the current literature reveals a lack of studies assessing the efficacy, safety, and appropriate dosing regimen of continuous omeprazole infusion in children with GI bleeding. This study aimed to evaluate the efficacy and safety of continuous IV omeprazole infusion in comparison to other therapeutic modalities in children. Methods This study is a single-center, retrospective chart review of children admitted to the PICU at King Faisal Specialist Hospital and Research Centre, Riyadh, Saudi Arabia. The treatment group included pediatric patients with GI bleeding and receiving omeprazole IV continuous infusion over ≥24 h while the control group included pediatric patients with GI bleeding managed using other therapies. Primary outcomes were the efficacy of omeprazole continuous infusion in stopping GI bleeding, and PICU length of stay (LOS). Secondary outcomes included instances of rebleeding post- therapy discontinuation, transfusion requirements, and the safety of omeprazole continuous infusion. Results The study included 81 critically ill pediatric patients, 22 of whom received continuous infusion omeprazole while 59 received other therapies. The results indicated that patients in the control group had a significantly shorter PICU LOS (8 vs. 18.5 days, p < 0.001) and bleeding episode (4 vs. 10.5 days, p < 0.001) than those in the treatment group. However, no significant differences were observed between the two groups regarding secondary outcomes. The treatment group had a significantly lower all-cause mortality rate during hospitalization compared to the control group (16 patients [72.7%] vs. 56 patients [94.9%], respectively, p = 0.005). Conclusion Empirical use of omeprazole continuous intravenous infusion in children with GI bleeding was not favorable in terms of shortening PICU LOS and duration of GI bleeding. Our study results provide evidence supporting the safety and tolerability of omeprazole continuous infusion. Additional larger studies are necessary to determine the implication of such results.